2021
DOI: 10.21831/pri.v4i1.44025
|View full text |Cite
|
Sign up to set email alerts
|

Career Adaptability and Work Engagement of Millennial Startup Employees

Abstract: This study aims to determine the level of career adaptability and work engagement and the effect of career adaptability on work engagement in millennial generation employees at a startup company. This type of research is ex post facto with a quantitative approach. The population of this study amounted to 34 employees who work at the startup company. This research is a population study; therefore, it uses the entire population of employees. The instrument uses a psychological scale of career adaptability and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Most of previous researchers referred to Savickas definition of career adaptability in their papers (Maggiori, Rossier and Savickas, 2017) (Tladinyane and Van der Merwe, 2015) (Haynie, Flynn and Herda, 2020) (Ghosh and Fouad, 2018) (Haryani, 2021). Career adaptability is defined as an individual's readiness and resources for handling current and anticipated tasks, transitions, and traumas in their occupational roles that alter their social integration (Savickas, 2005).…”
Section: Career Adaptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most of previous researchers referred to Savickas definition of career adaptability in their papers (Maggiori, Rossier and Savickas, 2017) (Tladinyane and Van der Merwe, 2015) (Haynie, Flynn and Herda, 2020) (Ghosh and Fouad, 2018) (Haryani, 2021). Career adaptability is defined as an individual's readiness and resources for handling current and anticipated tasks, transitions, and traumas in their occupational roles that alter their social integration (Savickas, 2005).…”
Section: Career Adaptabilitymentioning
confidence: 99%
“…A study from Tladinyane and Merwe (2015) on employees of insurance companies in South Africa concluded that there are significant differences in age and race groups in relation to career adaptability and employee engagement, so organizations need to recognize these biographical differences as a reference for engagement interventions and career counseling arrangements (Tladinyane & Van der Merwe, 2015). Research conducted on millennial employees in Indonesian startup companies shows that career adaptability affects millennial work engagement on the dimensions of concern and curiosity, but not on the dimensions of control and confidence (Haryani, 2021). Another study on career adaptability from Yang et al (2019) in China proves that career adaptability has a significant effect on work engagement, thereby predicting employee well-neing behavior (Yang et al, 2019).…”
Section: Career Adaptabilitymentioning
confidence: 99%